Placebo effect in treatment of pain associated with venous leg ulcers - Joss-Wichman, Ewa; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Venous leg ulcers constitute a major therapeutic and social problem. This chronic recurrent condition concerns mostly elderly patients, often suffering from a number of other diseases, thus adding to their disability. Lower leg pain is the most common subjective symptom of the disease. Ever higher doses of strong analgesic drugs are commonly used in treatment of leg ulcers, sometimes with poor pain relief. Own observations reveal the possibility of alleviating this pain with administration of placebo. The probable mechanism of analgesic action of placebo, associated with patient\'s belief in efficacy of administered drug, lies in stimulation of release of endogenous opiates and activation of reward centers within the central nervous system. Currently many studies are conducted concerning possible utilization of this psychological mechanism in treatment of various pain syndromes.